The role of exosomes in ischemic stroke - Ciecierski-Koźlarek, Hubert; Żurek, Urszula; Tołwiński, Ignacy; Kędzierska, Zofia; Szwed, Weronika; Antkowiak, Klaudia; Dadas, Klaudia; Świercz, Aleksandra; Małachowska, Dominika; Shved, Kateryna (Journal of Education, Health and Sport, 2023)
Introduction and purpose: Ischemic stroke is one of the leading causes of death and disability worldwide. There is an urgent need to develop new treatments and diagnosis. The aim of this review is to gather current knowledge on the potential use of exosomes in the diagnosis and treatment of ischemic stroke. This review was based on available data collected in the Pub Med database and Google Scholar web search engine, using the key words: „Exosomes”, „ischemic stroke” Description of the state of knowledge: Currently, thanks to the development of knowledge about molecular processes, many studies are conducted on drugs that could limit neurodegenerative processes and support repair processes. Many of the drugs that could be used in treatment show poor penetration through the blood-brain barrier. In studies, exosomes show good penetration through the blood-brain barrier, limit neurodegenerative processes and show neuroregenerative effects. Exosomes are characterized by low immunogenicity and toxicity, and the proteins contained in them are involved in neurogenesis, anti-apoptotic processes and synaptic transmission. In addition, studies have shown exosomes inhibit autophagocytosis and reduce neuronal damage. ​ Summary: Studies performed on animal models have shown the effectiveness of exosomes in the diagnosis and treatment of ischemic stroke. Further studies are needed to determine the efficacy and safety profile of exosomes in humans.